Kara pozbawienia wolności za przestępstwa skarbowe — uwagi co do jej ostatecznego charakteru - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article concerns selected problems relating to imprisonment in fiscal penal law. After a brief introduction to the topic, the analysis concerns the current regulations in this regard. The author draws attention to the amendments to the Fiscal Penal Code to increase deterrence with fiscal penal law. This applies mainly to recidivism in the fiscal penal law. As a result, imprisonment rather lost its ultimate nature. The article contains the proposals for amendments relating to imprisonment in the Fiscal Penal Code.
Keywords: imprisonment; Fiscal Penal Code; ultimate nature; recidivism in fiscal penal law